Case management of gastrointestinal cancer patients receiving chemotherapy under the normalization of COVID-19 prevention and control (新型冠状病毒肺炎疫情常态化防控下胃肠道肿瘤化疗患者的护理管理实践) - Huang Xiaoying (黄晓英); Yang Heng (杨姮) (中西医结合护理)
Objective To explore the effect of case management of gastrointestinal cancer patients with cancer receiving chemotherapy under the normalization of COVID-19 prevention and control. Methods According to the COVID-19 prevention and control guidelines issued by the National Health Commission, the case management of gastrointestinal cancer patients with chemotherapy was carried out through a multidisciplinary system. The study data from August 1, 2022 to September 30, 2020 are selected as the observation values, and the study date from June 1, 2012- July 31, 202022 as the reference values. The completion rate of chemotherapy and nursing satisfaction were compared between the two groups. Results From August 1 to September 30, 2022, the completion rate of chemotherapy was increased by 6. 51%(from 89. 53% to95. 74%%), and the nursing satisfaction was improved by 6. 01%(from 91. 86% to97. 87%%). Conclusion Under the normalization of COVID-19 prevention and control, the case management of gastrointestinal cancer patients was carried out to ensure the orderly and standardized chemotherapy and improve the quality of clinical care. (目的 探讨个案管理在新型冠状病毒肺炎常态化防控期间胃肠道肿瘤化疗患者中的应用效果。方法 2022年6月1日－2022年7月31日需行胃肠道肿瘤化疗患者共86例, 2022年8月1日－2022年9月30日需行胃肠道肿瘤化疗患者共94例。2022年8月开始实行个案管理措施。比较个案管理实施前后胃肠道肿瘤患者化疗完成率和护理满意度。结果 个案管理流程实施后, 患者化疗完成度95. 74%(90/94)、护理满意度97. 87%(92/94), 分别高于实施前的89. 53%(77/86)、91. 86%(79/86)。结论 新型冠状病毒肺炎疫情常态化防控期间, 通过对胃肠道肿瘤化疗患者实施全程个案管理, 在落实防控的基础上, 确保了化疗的有序性、规范化, 提高了临床护理质量。)